Computational investigation of the dynamic response of silicon carbide ceramic under impact loading. (1st September 2022) - Muhammad, Riaz; Khan, Numan; Hussain, Ghulam; Ullah, Nasim; Mohammad, Al-Sharef; Al Ahmadi, Ahmad Aziz
Abstract: It is estimated that by 2027, the global ballistic ceramic composites market would reach a value of US3.67 billion. Many nations are increasing their military spending in order to better safeguard their military personnel, which has resulted in a tremendous increase in the market. As a result of the growing need for lighter, stronger, and harder ballistics, SiC-based composites are predicted to be the most lucrative of all ceramic materials. The study describes a finite-element model for ceramic carbide based on Johnson and Holmquist's well-suited constitutive model for ceramics. The dynamic material tests of Strassburger et al [Strassburger, E., H. Senf, and H. Rothenhäusler, 1994 Fracture propagation during impact in three types of ceramics. Le Journal de Physique IV . 4: C8-653-C8-658.] were replicated computationally to develop further insight about the material behavior under impact loading. Materials . were simulated using the elastic properties and Johnson-Holmquist (JH-2) material models, respectively, for metal and ceramic materials. The stress distribution, damage progression, and failure of the material were accurately predicted by the results. The damage pattern, failure type, and method of failure are all examined as a result of altering projectile velocity. Computational data is utilized to verify the model's accuracy and offer insight into the ceramic's reaction to high strain.